2018
DOI: 10.1002/jsfa.9379
|View full text |Cite
|
Sign up to set email alerts
|

Biosorptive detoxification of zearalenone biotoxin by surface‐modified renewable biomass: process dynamics and application

Abstract: BACKGROUND Contamination of food, feed, beverages and even drinking water with biotoxins is a growing global concern because of their potential health risks. In this work, surface‐modified sugar beet pulp waste was used for the biosorptive removal of zearalenone biotoxin from contaminated aquatic media. RESULTS Infrared, Boehm titration, BET (Brunauer–Emmett–Teller) surface area and point of zero charge analysis were employed for surface characterization. Kinetic and equilibrium studies showed that biotoxin bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Adsorption at higher pH may be indicative of higher tendency of the phenolate ion toward the adsorbents. Similar results obtained in recent studies conducted on sugar beet pulp biomass in which higher adsorption was obtained at higher pH [34]. However in another study conducted on grapes pomace, author did not find any effect of pH change over the adsorption of ZEA [13].…”
Section: Effect Of Phsupporting
confidence: 85%
See 1 more Smart Citation
“…Adsorption at higher pH may be indicative of higher tendency of the phenolate ion toward the adsorbents. Similar results obtained in recent studies conducted on sugar beet pulp biomass in which higher adsorption was obtained at higher pH [34]. However in another study conducted on grapes pomace, author did not find any effect of pH change over the adsorption of ZEA [13].…”
Section: Effect Of Phsupporting
confidence: 85%
“…The maximum adsorption took place within the time period of 10-20 min and no further changes in the adsorption were noted beyond the 30 min. Previous studies of mycotoxins adsorption on bio adsorbents have reported 15-30 min required for maximum adsorption [11,13,34]. Smaller time for the adsorption is beneficial from point of view that it can sequester all of the toxin in GI tract before it enter into the blood of the animal and could be useful for vivo studies.…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…Biosorbents with a zeta potential value between −10 and +10 mV are neutral, while those with zeta potentials >+30 mV or <-30 mV are strongly cationic or strongly anionic, respectively. In the literature, various research groups have reported the zeta potential of different biosorbents used for the removal of mycotoxins ( 19 , 20 , 22 , 39 ). Table 4 summarizes the zeta potential values of the biomaterials used to adsorb aflatoxins.…”
Section: The Most Important Characterization Techniques For Biosorben...mentioning
confidence: 99%
“…In the literature, all of the biosorbents used for the adsorption of aflatoxins were characterized relative to its pHpzc by using the immersion technique. As an example, Akar et al ( 39 ) reported pHpzc values of 1.9 and 2.7 for natural and modified sugar beet pulp wastes, respectively. The chemically modified biosorbent was used as an efficient material for zearalenone removal.…”
Section: The Most Important Characterization Techniques For Biosorben...mentioning
confidence: 99%
“…Adsorption is a popular analytical technique for removing numerous organic and inorganic pollutants from wastewater. The abundance of adsorbents used in this method and their low-cost are two of the most significant advantages that led to the technique's popularity [6][7][8][9][10]. Clay minerals, one of the most abundant minerals, are excellent adsorbents in natural, composite, and modified forms and offer a number of advantages, including high specific surface area, nontoxicity, low-cost, and superior adsorption capabilities [11,12].…”
Section: Introductionmentioning
confidence: 99%